2023
DOI: 10.1177/13623613231154053
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of GABAergic interneuron pathology in autism are associated with intellectual impairment and stereotypic behaviors

Abstract: Autism spectrum disorder is a neurodevelopmental condition characterized by deficits in social communication and repetitive behaviors. How specific anatomical alterations contribute to the clinical profile of autism spectrum disorder remains largely uncharacterized. We have previously shown that parvalbumin-positive Chandelier cells, a specific type of GABAergic interneuron, are reduced in number in the autism spectrum disorder prefrontal cortex. Here, we assessed the relationship between interneuron pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 82 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…and decreased PV protein expression in the striatum ( Lauber et al, 2018 ) of Cntnap2 KO mice (ASD mouse model). In humans, reductions in PV+ Chandelier cells in the cortex was associated with RRB and motor stereotypies ( Dufour et al, 2023 ). In a different approach, a recent study found that PV+ cells in the DMS of Cntnap2, Shank3 and VPA mice are surrounded by perineuronal nets (extracellular matrix structures), and their degradation restored repetitive behaviors to normal levels ( Briones et al, 2022 ).…”
Section: Microcircuit Determinants Of Repetitive Behaviormentioning
confidence: 99%
“…and decreased PV protein expression in the striatum ( Lauber et al, 2018 ) of Cntnap2 KO mice (ASD mouse model). In humans, reductions in PV+ Chandelier cells in the cortex was associated with RRB and motor stereotypies ( Dufour et al, 2023 ). In a different approach, a recent study found that PV+ cells in the DMS of Cntnap2, Shank3 and VPA mice are surrounded by perineuronal nets (extracellular matrix structures), and their degradation restored repetitive behaviors to normal levels ( Briones et al, 2022 ).…”
Section: Microcircuit Determinants Of Repetitive Behaviormentioning
confidence: 99%
“…[74][75][76] Similarly, reduced number of PVIN in the prefrontal cortex has been reported in autism. 76,77 In accordance, optogenetic stimulation of PVIN in Alzheimer's, schizophrenia, and autism preclinical models has yielded promising outcomes. [78][79][80] On a different frontier, defective PVIN signaling has also been shown to be implicated in glioma cell proliferation.…”
Section: Beyond Epilepsymentioning
confidence: 99%